2007
DOI: 10.1039/b700421d
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional Raman and Raman optical activity correlation analysis of the α-helix-to-disordered transition in poly(l-glutamic acid)

Abstract: Rich and complex Raman scattering and Raman optical activity (ROA) spectra have been measured monitoring the pH induced alpha-helix-to-disordered conformational transition in poly(L-glutamic acid). Two-dimensional (2D) correlation techniques have been applied to facilitate a comprehensive analysis of these two complementary spectral sets. Synchronous contour plots have identified band assignments of alpha-helical and disordered conformations, and have revealed bands characteristic of changes in the protonation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 55 publications
0
53
0
2
Order By: Relevance
“…Recently, the pH-induced α-helix-to-disordered transition of poly-L-lysine was investigated by the 2D-ROA, 2D-Raman and hetero-correlation 2D-Raman approaches. [34] The analysis showed that unfolding began with α-helical regions of the polypeptide, exhibiting two distinct stages of α-helix melting. Amide III vibrations of the random coil structure are known to be more intense in Raman spectra as compared to IR spectra while the latter is more sensitive to the helical structure.…”
Section: Dcos Raman Hetero-correlation Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the pH-induced α-helix-to-disordered transition of poly-L-lysine was investigated by the 2D-ROA, 2D-Raman and hetero-correlation 2D-Raman approaches. [34] The analysis showed that unfolding began with α-helical regions of the polypeptide, exhibiting two distinct stages of α-helix melting. Amide III vibrations of the random coil structure are known to be more intense in Raman spectra as compared to IR spectra while the latter is more sensitive to the helical structure.…”
Section: Dcos Raman Hetero-correlation Studiesmentioning
confidence: 99%
“…[1,19,47] The presence of noise and a shifting baseline, [48] band shift and overlap, [1] the selection of the de-noising method, [48] different data preprocessing methods including mean-centering, auto-scaling and non-scaling, [48] selection of the reference spectrum, [25,49] the wavenumber range used for plotting, [34] etc. can dramatically change the appearance of 2D maps.…”
Section: Difficulties In Interpretation Of 2d Correlation Mapsmentioning
confidence: 99%
“…Recently, Pazderka and Kopecky have combined 2dCos with principal components analysis (PCA) in order to reduce noise and baseline distortions prior to generation of the 2d contour maps [94]. the ability of 2dCos RoA to reveal new structural information was shown by Ashton et al in their study on α-helix unfolding in the model homopolypeptide poly-L-glutamic acid [95], which distinguished between fraying of the ends of helices and unfolding of the core helical structure.…”
Section: Two-dimensional Correlation Analysismentioning
confidence: 97%
“…ROA spectroscopy has been applied to the native and nonnative proteins in solution in order to assign the ROA bands of proteins and to analyze their unknown secondary or higher-order structures, especially those of unfolded or denatured proteins which are difficult to analyze by other methods [28,32,[36][37][38][39][40][41][42][43][44][45][46][47][60][61][62]. Specific ROA bands of the proteins have been assigned to the peptide secondary structures in an empirical way based on the comparison of the crystal structure of the protein and its measured ROA spectrum in solution.…”
Section: Conformational Analyses Of Proteinsmentioning
confidence: 99%